PHARMACOECONOMIC STUDY OF VARIOUS BRANDS OF ANTI-EPILEPTIC DRUGS AVAILABLE CURRENTLY IN INDIA - Agrawal, Mehul; KUMAR, TARUN; MUJUMDAR, SWAPNIL; SAULAT, SAMAN AATIF (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: (a) Compiling a comprehensive list of the available dosage forms and strengths of various antiepileptic drugs marketed in India. (b) Calculating the percentage cost variation of individual drug formulations produced by different pharmaceutical companies. (c) Evaluating the percentage cost variation of these drugs. Methods: The cost of an exact drug (cost per 10 tablets) in the same strength and amount of forms being manufactured by different companies were got from the latest editions of “Current Index of Medical Specialties” and “Indian Drug Review.” The percentage price difference and cost ratio for each formulation were intended. Result: Among single drugs, the highest price variation was found in the drug pregabalin available in the form of capsules (75 mg and 150 mg), and a cost ratio of 6.64 and 5.87 was calculated which was significant. Among combination drugs, tablet Na valproate+valproic acid with the cost ratio of 1.91 was found to be the highest. Conclusion: Our study shows that there is very high price variation in some of the brands of anti-epileptic drugs. Generic prescribing should be promoted in the whole country by creating awareness and implementing proper regulatory guidelines.